RELATIVE IMPORTANCE OF FIBER PROPERTIES AFFECTING YARN HAIRINESS IN SOME EGYPTIAN COTTON VARIETIES - Kh.M.M Hussein; M.H . Mahmoud; A.A . Hassan (Arab Universities Journal of Agricultural Sciences, 2009)
undesirable, depending on the application for which the yarn is being used. Hairy yarns provide good heat retention and a softer hand (feel) for finished fabrics, and except for a few special cases, when it is an excessive degree of hairiness, yarn hairiness is an undesirable property in yarn and can cause serious problems in both yarn production and in subsequent textile processes. This search was carried out to investigate the most important fiber properties i.e. short fiber content (SFC w %), maturity ratio, micronaire value, uniformity index (UI %), fiber length (UHM) and fiber strength (g/tex) which correlated with yarn hairiness and also their relative contributions in yarn hairiness under study by using four Egyptian cotton varieties during season 2008, namely; Giza88, Giza86, Giza80 and Giza90 spun into carded ring and compact yarns at twist multiplier 3.6 and two  into counts according to the following: ring yarns were processed to carded yarns Ne 50 and 60. Compact yarns were also processed to carded yarns at the same counts. The most important results were: 1-  Yarns manufactured by the carded ring spinning frame are characterized by higher hairiness mean values in all studied varieties in comparison with those of carded compact frame. 2-   The correlation coefficients have positive signs and are very high between hairiness in yarns and short fiber content (SFC w %), on the contrary the correlation coefficients have negative signs being high or very high between maturity ratio, micronaire value, uniformity index (UI %), fiber length (UHM) and fiber strength (g/tex) and yarn hairiness in all varieties. 3-  Stepwise regression procedure was employed to determine the most effective independent variables which make the maximum contributions to the coefficient of determination (R²). The rate of improvement in yarn hairiness index due to decrease short fiber content (the larger the share of fibers in the shorter length the higher is the hairiness index), increase fiber strength (more mature fiber) and increasing fiber length (the larger the share of the fibers in longer length the lower is the hairiness index